HGG-24. NTRK-rearranged infantile gliomas of suprasellar/ optic pathway origin. (3rd June 2022) - Lazow, Margot A; Mathew, Mariam; Salloum, Ralph; Rodriguez, Diana P; Leonard, Jeffrey; Chi, Susan; Thomas, Diana; Cottrell, Catherine; Fouladi, Maryam; Boué, Daniel R
Abstract: BACKGROUND: Oncogenic fusions involving neurotrophic tyrosine receptor kinase (NTRK) have been identified across cancer types and represent potential therapeutic targets given availability of TRK inhibitors. Gliomas harboring NTRK fusions have been described most commonly in infants with high-grade histology and hemispheric tumor location, though there is emerging evidence suggesting clinical, histopathologic, and molecular heterogeneity. Herein, we present two cases of NTRK-rearranged suprasellar/ optic pathway gliomas. CASE DESCRIPTIONS: The first patient was diagnosed at 6 months old with an extensive suprasellar/ optic pathway tumor, treated with carboplatin/ vincristine, which initially responded but subsequently progressed. A biopsy was then performed, with pathology consistent with infiltrating piloid astrocytoma with anaplastic features (elevated mitoses and Ki-67 index); a BCAN-NTRK1 fusion was identified by RT-PCR and confirmed by Sanger sequencing. After further disease progression on vinblastine monotherapy, this patient began treatment with entrectinib (NCT02650401), with favorable clinical and radiographic responses thus far. The second patient was diagnosed with a large suprasellar/ optic pathway tumor at 3 years old, and underwent upfront partial resection, revealing similar infiltrating piloid/pilocytic astrocytoma with anaplastic features (elevated mitoses and Ki-67 index). A diagnosis of "midline" infantile high-grade glioma (HGG) was also considered, as with the former case. Sequencing demonstrated a SOX10-NTRK3 rearrangement, resulting in an integrated diagnosis of NTRK-fused infantile HGG, for which the patient recently started treatment with larotrectinib (NCT04655404). Both patients' fusions retain the entire kinase domain of respective NTRK partners, supporting oncogenicity, and neither tumor harbored additional somatic pathogenic variants (both lacked BRAF alterations). Methylation profiling did not confidently classify either tumor. CONCLUSIONS: NTRK-rearranged gliomas may present with primary suprasellar/ optic pathway involvement in infants. Given the potential to offer targeted therapy, testing for the presence of NTRK fusions should be strongly considered for infantile gliomas in any location, including midline, and across the histologic spectrum.